The ozone layer - Fisher, Marshall (New York : Chelsea House, 1992)
The ozone layer protects life on Earth from harmful ultraviolet radiation but this protective shield is being damaged by chlorofluorocarbons and other pollutants that are now being generated on the Earth.
Includes bibliographical references (p. 99-100) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
8.9
5-8
Keywords: Chlorofluorocarbons -- Environmental aspects -- Juvenile literature; Environmental protection -- Juvenile literature; Man -- Influence on nature -- Juvenile literature; Ozone layer -- Juvenile literature; Chlorofluorocarbons; Ozone layer; Chlorofluorocarbons; Ozone layer